Insufficient LGBTQ+ education across disciplines suggested by national survey of health professionals in training - Lexie Wille; Tess Jewell; Atticus Wolfe; Emily Peterson; Aileen Shaughnessy; Cole Roblee; Alex Strader (PLoS ONE, 2025)
Health professionals often feel underprepared to treat patients who identify as lesbian, gay, bisexual, transgender, and/or queer (LGBTQ+). Additionally, lack of access to professionals who are knowledgeable about LGBTQ+ inclusive care contributes to the myriad of health disparities experienced by LGBTQ+ communities. This cross-sectional survey study explores the preparedness of healthcare profession trainees for caring for LGBTQ+ patients by quantifying the hours and quality of training health profession trainees receive in LGBTQ+ education across disciplines. We surveyed US-based health professionals in training (HPiT) across disciplines (N = 155) on their training programs’ LGBTQ+-specific curricula and educational opportunities. Ordered logistic regression analysis assessed the relationship between the number of hours of LGBTQ+-specific education and other discipline, organization, and individual factors. Respondents reported an average of 4.75 (SD = 3.04) hours devoted to LGBTQ+-specific education. Physician assistant trainees reported receiving the highest number of hours of LGBTQ+-specific education (M = 6.63, SD = 1.98), followed by psychology (M = 5.30, SD = 3.54), medical (M = 5.12, SD = 3.38), nursing (M = 4.17, SD = 3.28), and trainees in other health fields (M = 3.88, SD = 2.47). Across all disciplines, trainees rated their LGBTQ+-specific education on average as “good”. Despite rising awareness, the quantity and quality of dedicated LGBTQ+-specific education remains concerningly low across all measured disciplines and US regions. Future research must investigate strategies to overcome common barriers to increasing LGBTQ+ education in health professions training by maximizing the impact of limited hours through integrating LGBTQ+ content into existing materials, supporting trainee leadership, and implementing institutional support for educators teaching LGBTQ+ content. Regulatory bodies must reconsider the current guidance for LGBTQ+ education quantity and quality to advise institutions on best-practice guidelines to prepare trainees for LGBTQ+ patient care.